Technology in F&B SMEs: A conceptual framework to enhance business performance among SME F&B - Yusuf, Yusni Munirah; Ab Rahman, Siti Maziah; Bustaman, Hasnun Anip (Journal of Islamic, Social, Economics and Development, 2025)
This paper represents a conceptual framework that explores the readiness and adoption of technology in food and beverages industry mainly among small and medium enterprise. In technology era nowadays, applying technology within a business has become an essential need for the business to survive in rapidly changing market environment. This study examines the relationship between technology readiness and technology adoption impact on business performance of food and beverages in small and medium enterprise, evolved around the technology acceptance model (TAM) and thus, serves as framework foundation for both academic research and practical implication for the future researcher.